1990
DOI: 10.3133/pp1502
|View full text |Cite
|
Sign up to set email alerts
|

Microbanded manganese formations; protoliths in the Franciscan Complex, California

Abstract: The Buckeye manganese deposit, 93 km southeast of San Francisco in the California Coast Ranges, preserves a geologic history that provides clues to the origin of numerous lenses of manganese carbonate, oxides, and silicates that occur with interbedded radiolarian chert and metashale of the Franciscan Complex. Compositionally and mineralogically laminated Mn-rich protoliths were deformed and dismembered, in a manner that mimics in smaller scale the deformation of the host complex, and then were incipiently meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1992
1992
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…Minerals containing B or W have been reported from several bedded manganese deposits in Japan, such as hübnerite, tinzenite, and wiserite (e.g., Watanabe et al 1970), although no such minerals have been recognized in this study; the reasons for their absence remain unclear. Huebner & Flohr (1990) showed a positive correlation between tungsten contents and modal proportion of gageite in the cherthosted manganese ores of the Franciscan Complex. The absence of tungsten in the Nagasawa ores may imply the absence of specific precursor minerals such as gageite.…”
Section: Origin Of the Minor Elementsmentioning
confidence: 99%
See 3 more Smart Citations
“…Minerals containing B or W have been reported from several bedded manganese deposits in Japan, such as hübnerite, tinzenite, and wiserite (e.g., Watanabe et al 1970), although no such minerals have been recognized in this study; the reasons for their absence remain unclear. Huebner & Flohr (1990) showed a positive correlation between tungsten contents and modal proportion of gageite in the cherthosted manganese ores of the Franciscan Complex. The absence of tungsten in the Nagasawa ores may imply the absence of specific precursor minerals such as gageite.…”
Section: Origin Of the Minor Elementsmentioning
confidence: 99%
“…Momoi et al (1988) identified clay minerals enclosing spherulitic rhodochrosite from the Komaoka mine, Japan, as interlayered chloritesaponite. Huebner & Flohr (1990) The formation of pyroxmangite continued until rhodochrosite was completely consumed. The sequence of reactions is consistent with the petrographic observation that pyroxmangite veins occasionally fill the interstices of garnet-1 crystals (Fig.…”
Section: Protoliths and Chemical Processes In Contact Metamorphismmentioning
confidence: 99%
See 2 more Smart Citations
“…The occurrence of native copper in the Skyring Creek material is interesting, as native copper occurs in the Blue Jay Mine, Franciscan Complex, California, in association with hausmannite, braunite and neotocite (Huebner and Flohr 1990). These investigators suggest that this deposit is a product of sea floor volcanism.…”
Section: Manganese Genesismentioning
confidence: 95%